Pyro-phototronic effect: An effective route toward self-powered photodetection. (March 2023) - Sahare, Sanjay; Ghoderao, Prachi; Sharma, Manish Kumar; Solovan, Mykhailo; Aepuru, Radhamanohar; Kumar, Manjeet; Chan, Yue; Ziółek, Marcin; Lee, Shern-Long; Lin, Zong-Hong
Abstract: The Photodetector (PD) refers to an energy harvesting device that can directly convert light energy into electric current. Such a device has been widely used in different applications ranging from optoelectronics, and biomedical, surveillance to environmental monitoring. It consists of a heterojunction made up of various ceramic and hybrid materials. Especially, Self-powered PDs have attracted tremendous attention due to their significance in fundamental science, day-to-day life, and commercial value. Importantly, self-powered devices can reduce the dependency on an external power supply, making them self-sustainable for powering smart devices. Moreover, the pyro-phototronic effect (PPE) in self-powered PDs that boosts device performance beyond expectations is appealing thanks to the modulation of photo-generated charge carrier separations, transportation, and extraction. This review assesses the fundamental mechanism behind the PPE and discusses the recent progress of fundamental research in various nanostructured materials as well as their heterojunctions. The PPE remains virtually underexplored in optoelectronic devices. It is essential to comprehensively provide both theoretical and experimental overviews to the relevant researchers. The PPE has many merits such as excellent photoresponsivity, fast photo response rate, very low dark current, and a large light on/off ratio of self-powered PDs. Furthermore, the synergism of ferro- and piezo-phototronic effects gives rise to efficient self-powered PDs. Here, we discuss the critical challenges and perspectives for PPE in self-powered PDs for future developments. This comprehensive review is foreseen to offer researchers a precise path to employing PPE in conjunction with the new structure and device designs for enhancing photodetection performance in the future. Graphical Abstract: The graphical abstract depicted a pyro-phototronic effect that synergistically combined with different effects, and revealed high performance in the device for diverse applications. ga1 Highlights: The pyro-phototronic effect (PPE) is a crucial strategy to enhance the device's performance beyond our expectations. The fundamental research and its progress in various nanostructured materials and heterojunctions have been discussed. The synergistic effect of Ferro- and piezo-phototronic effects highlights efficient and high-performing self-powered PDs. Critical challenges and perspectives for the PPE in self-powered PDs for future development have been exploited. It provides a comprehensive theoretical and experimental overview to the relevant researchers.